Perilymphatic fistula: a historical overview of publication trends - Perdomo, Dianela; Schoo, Wesley W.; Stemme, Rachel; Schoo, Desi P.; Carey, John P.; Ward, Bryan K. (Frontiers in Audiology and Otology, 2024)
Background: Perilymph fistula (PLF) can cause symptoms of dizziness, vertigo, and fluctuating hearing. We hypothesized that publications on PLF have decreased in recent years relative to other inner ear disorders with overlapping symptoms.Methods: We performed a Scopus search using the terms "perilymphatic fistula" OR "perilymph fistula," limited to original studies or reviews involving human subjects published in English before 2022. We noted the senior author's institution, country affiliation, and publishing journal. The Kendall rank correlation coefficient test was used to analyze the trend of each variable over the past 30 years. Using the same search strategy, we compared these data to those from vestibular neuritis (VN), Meniere's disease (MD), superior semicircular canal dehiscence (SSCD) and benign paroxysmal positional vertigo (BPPV).Results: 698 PLF publications were returned. The top publishing country was the United States (n=334), the top publishing journal was the American Journal of Otology/Otology and Neurotology (n=68), and the top publishing institution was the University of Pittsburgh (n=15). In the past 30 years (n=501), there was no trend in the frequency of annual PLF publications (τ=-0.150, p=0.265). Still there were positive trends in publications on vestibular neuritis (τ=0.724, p<0.001), Meniere's disease (τ=0.587, p<0.001), superior canal dehiscence syndrome (τ=0.840, p<0.001), and benign paroxysmal positional vertigo (τ=0.882, p<0.001) 5,398 PLF cases were identified, of which 4,356 specified the etiology; the majority identified an inciting insult (74.8%, n=3,257).Conclusions: The absence of diagnostic criteria for PLF may hinder its appeal to researchers as similar syndromes have had diagnostic consensus documents set forth. Given the greater number of cases with inciting insults, efforts to define a diagnostic criterion should focus on this subtype.